Fitness testing battery for rugby league: Obtaining meaningful information from the data - Banoocy, N. K. (Journal of Australian Strength and Conditioning, 2018)
The recommended tests for rugby league players include body mass, height, 7-site skinfold measurement, countermovement jump, squat jump, 5-0-5 change of direction speed test, 40-meter sprint test, 1RM squat and bench press, and 30-15 Intermittent Fitness Test.